Initiatives on "sport for development and peace" in Japan: A focus in trends in the field, policy, and research - Yamahira, Y.; Saito, K.; Shiraishi, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
Drawing on 3 perspectives presented in previous studies - "the field," "policy," and "research" - this study aimed to highlight trends in Japan's "Sport for Development and Peace" (SDP) program. Moreover, by examining the relationships among the 3 perspectives, suggestions for the future development of SDP in Japan were sought. Overall, this study attempted to summarize trends in policy, research, and the field, as they relate to Japan's SDP program, and the following 4 conclusions were reached: 1) Japan-based NGOs are expanding, thanks to opportunities provided by Sport for Tomorrow (SFT). 2) Many policies are interrelated, although the institutions that manage them differ. 3) One trend in Japanese SDP research is the growing number of studies examining disability and gender in regions such as Laos, Malaysia, and Thailand. 4) Regarding the relationship between "policy" and "the field," one Japan-based NGO has been developing SDP activities under multiple policies. As for the relationship between "policy" and "research," many studies have focused on JICA Overseas Cooperation Volunteers and SFT. Lastly, the relationship between "research" and "the field" has been limited by a paucity of studies on NGOs. Additionally, this study provided 4 directions for the future development of Japan's SDP program. 1) The SDP activities of Japan-based NGOs need to be scrutinized, and support must be provided to NGOs that are not yet engaged in SDP activities. 2) Greater public awareness of Japan`s domestic SDP policies is required. 3) A growing number of studies are expected to examine the relationship between SDGs and sports. 4) Assuming the continuation of Japanese SDP policies, expectations with regard to NGOs will grow. Connections between universities and Japanese SDP policy require the establishment of a clear relationship between the two. Furthermore, research collaborations between NGOs and universities can be expected in the future.